A várossá nyilvánítás elvi kérdései, potenciális városok az Északnyugat-Dunántúlon - Csapó, Tamás; Kocsis, Zsolt (Tér és Társadalom, 1997)
In Hungary the network of the towns has not yet developed fully, making the declaration of another 50-80 settlements as towns justifiable in the coming 10-15 years. Most of the settlements to be declared as towns can be found in regions dominated by small and tiny villages, i.e. in North Hungary and Northwest Transdanubia. In this latter region, 15 settlements should be ranked as towns in two steps. In the first phase (until the year 2000) Jánossomorja, Tét, Bük, Répcelak, Devecser, Herend, Zalalövő and Komár, in the second phase (until 2005-2010) the settlements of Beled, Pannonhalma, Jánosháza, Őriszentpéter, Nagyvázsony, Balatonfűzfő and Bak should be given town status. This would not modify the spatial structure of the region to a large extent, but the new small towns would significantly decrease the number and surface area of the regions that are in want of towns at the moment, although they will probably be too weak for a long time to eliminate the inner peripheries. The town rank of the aforementioned small centres will only bring real results if they develop and expand in their functions. With respect to retail trade and administration, most of them can now be regarded as towns, central places, but their roles in health care, economy, especially employment has to be strengthened. The single most important issue, however, is settling down secondary education in these settlements. The would-be towns thus need to develop in the first place their institutional infrastructure and their own economy, and only in the second place the communal infrastructure, as this is also the priority order of the functions which make them towns of their environment. The acquisition of the town status should continue to be conditional, but the criteria should be flexible, suited to the differences in the regional and seftlement network. The desirable number of population is around 2 000, but this criterion, as each of the others, should not have an absolute right of veto. A criterion of special importance should be the central function, spatial organising power of any seftlement. The criteria of obtaining the town status should be separated. A system of criteria based primarily on statistical and quantitative-qualitative indices should be set for those settlements in the case of which it is only to the advantage of the given settlement to become a town, as in many cases they have no real catchment area (large villages and old agricultural towns in the Great Hungarian Plain, sleeping villages of the Budapest agglomeration); another set of conditions should be defined for those settlements where their region and surrounding settlements have a vested interest in the given settlements obtaining town status, maybe an interest bigger than they themselves have. In the process of the declaration as town the role of the medium level has to be strengthened. Becoming a town should be a planned process which also appears in the small regional, county and regional development concepts. The initiatives should of course continue to come from the boltom, the seftlement level.